Role of steroids in critically-ill sepsis patients: a review article and literature to review - Mohsin Mirza; Maryam Zafar; Mariam Siddiqui; Anum Abbas; Joseph Nahas; Muazzam Mirza; Abubakar Tauseef (Greater Baltimore Medical Center, 2021)
Sepsis, a life-threatening condition, commonly affecting critically ill patients, is a major cause of death worldwide. It is thus of great importance to determine the optimum management to cure this condition. This review article summarizes the role and eﬀects of corticosteroids in the treatment of sepsis and septic shock, and to determine its mortality benefits. We used PubMed, Google scholar, Scopus, and Embase databases for literature review, and terminologies commonly searched were 'sepsis', 'septic shock', 'therapeutic use' and 'corticosteroids'. In this review article, we reviewed a total of eight different articles being done in last 10 years, relevant to the clinical outcome and eﬀects of corticosteroids. Among those, two demonstrated improved clinical outcomes, two showed both improved clinical outcomes and decreased mortality, three showed increased adverse eﬀects, and the remaining one showed unequivocal results.